78.3k views
5 votes
How do you do: -6(6a-5)=-2(8-5a)

User ASR
by
5.5k points

1 Answer

2 votes

Answer:

a = 1

Explanation:

1. distribute the -6 on the left into the parentheses. you should get -36a + 30.

2. on the side right of the =, distribute the -2 to get -16 + 10a.

now it should look like -36a + 30 = -16 + 10a.

3. move the terms over to isolate the a value. subtract 30 to the right side to get -46 (-36a=-46+10a)

4. move the 10a on the right to the left by subtracting it to the other side.

(-46a=-46)

5.divide by -46 to get a=1

User Franz Wexler
by
5.2k points